Pattern Of Sexually Transmitted Infections And Sexual Behavior In Patients With Genital Symptoms - M Gyawalee; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Sexually transmitted infections are a major cause of acute illness, infertility, long-term disability, economic loss and death throughout the world. Despite the availability of effective treatment and preventive measures, incidence of STIs is increasing even in developed countries. STIs, acting as a facilitator for the spread of HIV have become a globally important issue at present context.